MANAGEMENT OF THE POST-WAR COMPETITIVE TRANSFORMATION OF TERRITORIAL COMMUNITIES (INNOVATIVE ECONOMY, 2026)
Krysko Zh.L. MANAGEMENT OF THE POST-WAR COMPETITIVE TRANSFORMATION OF TERRITORIAL COMMUNITIESPurpose. The aim of the article is to substantiate the theoretical and practical foundations of the management of the post-war competitive transformation of territorial communities in Ukraine based on the adaptation of the Marshall Plan principles and the development of a territorial development management model in competitive environment conditions.Methodology of research. The research employed general scientific and special methods, including: analysis and synthesis – to generalize scientific approaches to post-war recovery, territorial competitiveness, and strategic community development management; a systems approach – to consider a territorial community as an integrated system; the abstract and logical method – to formulate theoretical generalizations and develop a management model for the post-war competitive transformation of territorial communities; structural and functional analysis – to determine the interrelationships between the components of the model and the mechanisms of their implementation; comparative analysis – to study the possibilities of adapting the Marshall Plan principles to the current conditions of Ukraine’s development; and the graphical method – to visualize the management model of the post-war competitive transformation of territorial communities.Findings. The article substantiates that the post-war recovery of territorial communities should be considered not only as a process of eliminating the consequences of destruction, but also as a comprehensive system of competitive territorial development aimed at ensuring long-term sustainability, investment attractiveness, and managerial capacity. It has been established that under decentralization conditions territorial communities are gradually transforming into independent actors within a competitive environment, competing for investments, international assistance, and human capital, grant resources, and relocated businesses. It has been proven that the effectiveness of post-war transformation depends not only on the scale of financial support, but primarily on the quality of strategic management, the level of institutional capacity, transparency in resource utilization, and the ability to ensure structural changes. A management model for the post-war competitive transformation of territorial communities has been proposed.Originality. A management model for the post-war competitive transformation of territorial communities has been developed, based on the integration of strategic, investment-project, digital, social and human resource, and partnership management components, allowing the competitiveness of a territorial community to be considered as the result of their comprehensive interaction. The approach to managing the development of territorial communities has been improved through the adaptation of the Marshall Plan principles to the current conditions of Ukraine’s post-war recovery, taking into account digitalization of management, human capital development, and partnership interaction.Practical value. The proposed model can be used by local self-government authorities to develop strategies for the post-war development of territorial communities, improve strategic management systems, develop grant and investment-project management, increase the effectiveness of digital governance, and ensure partnership interaction in territorial recovery processes.Key words: territorial communities, post-war recovery, transformation, development management, public administration, digitalization, community competitiveness, Marshall Plan.
Keywords: territorial communities; post-war recovery; transformation; development management; public administration; digitalization; community competitiveness; Marshall Plan